Humanities and the Social Sciences in the International Polar Year: Issues and Projects from a Swedish Perspective - Sörlin, Sverker; Avango, Dag (Journal of Northern Studies, 2007)
In this article, we present research and other International Polar Year (IPY) related activities within the humanities and the social sciences with an emphasis on Sweden. The three previous IPYs in 1882–83, 1932–33, and 1957–58 (IGY) were almost exclusively a domain for the natural sciences. The inclusion of the humanities and social sciences, as well as the involvement of Arctic peoples, is one of the major developments in the present IPY – a recognition of the fact that the polar areas are the home of people and scenes for human action and interaction of global importance. There are several IPY research projects with Swedish participation under way, on themes such as governance and adaptation of human-environment systems, industry and science in the field, social strategies of Arctic indigenous peoples, and North Atlantic diplomacy. There are also a number of activities within outreach and education that will present the pressing issues of polar science to students, policy makers and the general public. The IPY effort is the largest ever undertaken by the Swedish social sciences and humanities in and on the polar regions in such a short period of time. The research is conducted at several universities, notably Gothenburg, Umeå, and the Royal Institute of Technology. It will leave a legacy of importance for the polar research community as well as for the peoples of the North.